Methodology and fieldwork - Srivastava, Vinay K. (New Delhi : Oxford University Press, 2004)
Contributed articles chiefly with reference to India.
Keywords: Sociology -- Fieldwork; Sociology -- Methodology; Ethnology -- Fieldwork; Ethnology -- Methodology